2018
DOI: 10.21815/jde.018.123
|View full text |Cite
|
Sign up to set email alerts
|

Dentists’ Perceptions of Their Peer Learning Experiences in Dental School and Effects on Practice

Abstract: Peer‐assisted learning (PAL) has been found in medical, nursing, and dental education research to aid in preparing students to develop clinical judgment, leadership, and teamwork skills. This study sought to extend that research by assessing the effect of PAL on dentists in practice. The aim of this study was to ask practicing dentists who were clinically trained with PAL in dental school for their perceptions of the effects and value of that training for their patient care, team relations, and professional de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…The responses of participants in this study seemed to reflect the current evidence for peer‐learning strategies, where they provide moral support and recognize peers as a legitimate source of learning 30,31 . Earlier research suggests that dentists trained in the peer‐learning model support this and agree that it enhances learning among the students, and provides students with teaching experience and social skills, which could help their teamwork, leadership, and professional development 32,33 . However, problems have been noted, with "individual" different personalities and learning styles of hindering such a system 34 .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The responses of participants in this study seemed to reflect the current evidence for peer‐learning strategies, where they provide moral support and recognize peers as a legitimate source of learning 30,31 . Earlier research suggests that dentists trained in the peer‐learning model support this and agree that it enhances learning among the students, and provides students with teaching experience and social skills, which could help their teamwork, leadership, and professional development 32,33 . However, problems have been noted, with "individual" different personalities and learning styles of hindering such a system 34 .…”
Section: Discussionmentioning
confidence: 65%
“…30,31 Earlier research suggests that dentists trained in the peer-learning model support this and agree that it enhances learning among the students, and provides students with teaching experience and social skills, which could help their teamwork, leadership, and professional development. 32,33 However, problems have been noted, with "individual" different personalities and learning styles of hindering such a system. 34 The findings of the current study favor pairing students only in the junior years, where students are generally lacking in clinical exposure and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies reviewed, Qualtrough (2001) found that 63 % of students stated that efficiency was one of the most relevant advantages of working with a dental assistant (19). However, in another study, 21 % considered that the technique did not facilitate time management during the appointment (20). At the University of Malaysia, more than 95 % of the students considered that they learned from their partner and that clinical procedures were carried out more easily under this modality.…”
Section: Benefits Of the Methods To Train General Dentistsmentioning
confidence: 99%
“…Similarly, the majority of the students surveyed consider that the mentor-apprentice relationship motivated them to learn (24) and even enjoyed teaching others and felt comfortable with the role of leader. 86.2 % recommended peer-assisted learning (20). However, 15 % of those surveyed stated that this technique negatively affects learning (20).…”
Section: Benefits Of the Methods To Train General Dentistsmentioning
confidence: 99%
See 1 more Smart Citation